Positive electrode active material and positive electrode containing the same

JP2025503126APending Publication Date: 2025-01-30LG CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024543539
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-20
Filing Date
2023-05-22
Publication Date
2025-01-30

AI Technical Summary

Benefits of technology

【0027】 本発明による正極活物質は、前記正極活物質を正極活物質層の全重量に対して80重量%以上含む正極活物質層を含む正極を、圧延後の正極活物質層の密度が2.7g/cm3以上になるように圧延した後、正極活物質層をXRDで分析した時に、2θ 10゜~90゜区間で確認されたすべてのピークの面積に対する(003)ピークの面積の比率が30%以上を満たし、正極に適用する時に、正極活物質の膨張が抑制されることから、これを含む電池の初期抵抗特性および寿命特性を改善することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025503126000001_ABST
    Figure 2025503126000001_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material capable of realizing a battery having improved initial resistance characteristics and life characteristics, and a positive electrode including the same. The positive electrode active material is in the form of a single particle, and the positive electrode includes a positive electrode active material layer including the positive electrode active material in an amount of 80% by weight or more based on the total weight of the positive electrode active material layer. The positive electrode active material layer is rolled to have a density of 2.7 g / cm. 3 and a positive electrode including the same, wherein when the positive electrode active material layer is analyzed by XRD after being rolled to the above-mentioned degree, the ratio of the area of ​​the (003) peak to the area of ​​all peaks observed in the 2θ 10° to 90° range is 30% or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0062288 filed on May 20, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a positive electrode active material in a single particle form and a positive electrode containing the same. [Background technology]

[0003] Recently, with technological development and increased demand for mobile devices and electric vehicles, the demand for secondary batteries as an energy source has increased dramatically.

[0004] A lithium secondary battery generally comprises a positive electrode, a negative electrode, a separator and an electrolyte, and the positive electrode and the negative electrode contain active materials capable of intercalating and deintercalating lithium ions.

[0005] On the other hand, the positive electrode active material used in a lithium secondary battery generally has the form of spherical secondary particles formed by agglomeration of several hundred fine primary particles of submicron size. However, the positive electrode active material in the form of secondary particles has a problem that the secondary particles break as the aggregated primary particles separate during repeated charging and discharging, resulting in a deterioration of battery characteristics.

[0006] In order to solve these problems, development of single particle positive electrode active materials has been actively carried out, but when an electrode is manufactured using a single particle positive electrode active material, it is difficult to align the c-axis direction, which is the main expansion direction of the single particle positive electrode active material, as desired or to quantify the degree of alignment. On the other hand, if the c-axis direction, which is the main expansion direction of the single particle positive electrode active material, is not aligned and exists randomly, problems such as a decrease in battery life characteristics, a decrease in capacity, and a decrease in output occur. Therefore, a technology to solve this problem is required. Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a positive electrode active material capable of realizing a battery having improved initial resistance characteristics and life characteristics, and a positive electrode including the same. [Means for solving the problem]

[0008] In order to solve the above problems, the present invention provides a positive electrode active material and a positive electrode containing the same.

[0009] (1) The present invention relates to a positive electrode active material in the form of a single particle, and to a positive electrode including a positive electrode active material layer containing the positive electrode active material in an amount of 80% by weight or more based on the total weight of the positive electrode active material layer, the positive electrode active material layer being rolled so that the density of the positive electrode active material layer after rolling is 2.7 g / cm 3 When the positive electrode active material layer is analyzed by XRD after being rolled to the above value, the ratio of the (003) peak area to the areas of all peaks observed in the 2θ 10° to 90° range is 30% or more.

[0010] (2) The present invention provides a cathode active material according to the above (1), wherein, when a cathode active material layer before and after rolling of the cathode is analyzed by XRD, the ratio difference of the area of ​​a (003) peak to the areas of all peaks observed in the 2θ 10° to 90° range is 10% or more.

[0011] (3) The present invention provides a positive electrode active material according to (1) or (2) above, wherein the single-particle positive electrode active material has a ratio of the length in the a-axis direction of the crystal to the length in the c-axis direction of the crystal that is greater than 1.

[0012] (4) The present invention provides a positive electrode active material according to any one of the above (1) to (3), wherein the single-particle positive electrode active material is composed of 1 to 50 single crystal particles.

[0013] (5) In the present invention, in the above (4), the single crystal particles have an average particle size (D EBSD) is 0.1 μm to 10 μm.

[0014] (6) The present invention provides a positive electrode active material according to any one of the above (1) to (5), wherein the single particle positive electrode active material is a lithium transition metal oxide containing nickel (Ni), cobalt (Co), and manganese (Mn).

[0015] (7) The present invention provides a positive electrode active material according to the above (6), wherein the lithium transition metal oxide contains 60 mol % or more of nickel (Ni) among all metals other than lithium.

[0016] (8) The present invention provides a positive electrode active material according to the above (6) or (7), wherein the lithium composite transition metal oxide has a composition represented by the following chemical formula 1: [Chemical formula 1] Li a Ni b Co c Mn d M 1 e O2 In the above Chemical Formula 1, M 1 is one or more selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S; 0.90≦a≦1.1, 0.60≦b<1.0, 0 <c<0.40、0<d<0.40、0≦e≦0.10、b+c+d+e=1である。

[0017] (9) The present invention provides a positive electrode comprising a current collector and a positive electrode active material layer located on the current collector, the positive electrode active material layer comprising the positive electrode active material according to any one of (1) to (8) above.

[0018] (10) The present invention provides a positive electrode according to the above (9), wherein, when a positive electrode active material layer before and after rolling is analyzed by XRD, the ratio difference of the area of ​​a (003) peak to the areas of all peaks observed in the 2θ 10° to 90° range is 10% or more.

[0019] (11) In the present invention, in the above (9) or (10), when an angle between a lithium migration path of the positive electrode active material in the form of a single particle and an axis parallel to an upper surface of the current collector is θ, the angle is (cosθ) 2 A positive electrode having a value of 0.6 or more is provided.

[0020] (12) The present invention provides a positive electrode according to any one of (9) to (11), wherein the single-particle positive electrode active material has a c-axis direction of a crystal aligned in a direction perpendicular to an upper surface of a current collector.

[0021] (13) The present invention provides a positive electrode according to any one of the above (9) to (12), wherein the single-particle positive electrode active material has a ratio of the length in the a-axis direction of a crystal to the length in the c-axis direction of the crystal that is greater than 1.

[0022] (14) The present invention provides a positive electrode according to any one of the above (9) to (13), wherein the positive electrode active material in a single particle form is composed of 1 to 50 single crystal particles.

[0023] (15) In the present invention, in the above (14), the single crystal particles have an average particle size (D EBSD ) is 0.1 μm to 10 μm.

[0024] (16) The present invention provides a positive electrode according to any one of the above (9) to (15), wherein the positive electrode active material in a single particle form is a lithium transition metal oxide containing nickel (Ni), cobalt (Co), and manganese (Mn).

[0025] (17) The present invention provides the positive electrode according to the above (16), wherein the lithium transition metal oxide contains 60 mol % or more of nickel (Ni) among all metals other than lithium.

[0026] (18) The present invention provides a positive electrode according to the above (16) or (17), wherein the lithium composite transition metal oxide has a composition represented by the following Chemical Formula 1: [Chemical formula 1] Li a Ni b Co c Mn d M 1 e O2 In the above Chemical Formula 1, M 1 is one or more selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S; 0.90≦a≦1.1, 0.60≦b<1.0, 0 <c<0.40、0<d<0.40、0≦e≦0.10、b+c+d+e=1である。 Effect of the Invention

[0027] The positive electrode active material according to the present invention is a positive electrode including a positive electrode active material layer containing the positive electrode active material in an amount of 80% by weight or more based on the total weight of the positive electrode active material layer, the positive electrode active material layer being rolled so that the density of the positive electrode active material layer after rolling is 2.7 g / cm 3 When the positive electrode active material layer is analyzed by XRD after rolling to the above range, the ratio of the (003) peak area to the areas of all peaks observed in the 2θ 10° to 90° range is 30% or more. When used in a positive electrode, the expansion of the positive electrode active material is suppressed, thereby improving the initial resistance characteristics and life characteristics of a battery including the same.

[0028] In the positive electrode according to the present invention, when the positive electrode active material layer is analyzed by XRD after rolling the positive electrode, the ratio of the area of ​​a (003) peak to the area of ​​all peaks observed in the 2θ 10° to 90° range is 30% or more, and the c-axis direction of the crystal structure, which is the contraction / expansion direction of the positive electrode active material crystals contained in the positive electrode active material layer, is aligned in a direction perpendicular to the upper surface of the current collector, thereby suppressing the expansion of the positive electrode active material, thereby improving the initial resistance characteristics and life characteristics of a battery including the same. [Brief description of the drawings]

[0029] [Figure 1] 1 is a SEM image of the positive electrode active material of Example 1. [Diagram 2] 1 is a SEM image of the positive electrode active material of Comparative Example 1. [Diagram 3] 1 is an SEM image of the positive electrode active material of Comparative Example 3. [Figure 4] 1 shows XRD data of positive electrode active material layers before and after rolling of positive electrodes including the positive electrode active materials of Examples 1 and 2 and Comparative Examples 3 and 4. [Diagram 5] 1 is an EBSD Band Contrast (BC) image of a cross section of a positive electrode including the positive electrode active material of Example 1. [Figure 6] FIG. 2 is a diagram showing the angle between the c-axis direction vector (Euler angle) of a crystal grain and a directional vector perpendicular to the electrode (= the angle between the lithium migration path (Li path) and a directional vector parallel to the electrode). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0030] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of ​​the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.

[0031] In this specification, the terms "including," "comprising," or "having" are intended to specify the presence of embodied features, numerals, steps, components, or combinations thereof, but are not intended to preclude the presence or additional possibility of one or more other features, numerals, steps, components, or combinations thereof.

[0032] As used herein, the term "on" is meant to include not only when one structure is formed immediately on top of another structure, but also when a third structure is interposed between the structures.

[0033] In this specification, the term "single-particle positive electrode active material" refers to a positive electrode active material consisting of 50 or less single crystal particles, which is a concept that is contrasted with a spherical secondary particle positive electrode active material formed by agglomeration of several hundred primary particles produced by a conventional method. Specifically, in the present invention, the single-particle positive electrode active material may be one single crystal particle, or may be in the form of an aggregate of 2 to 50, 2 to 40, 2 to 30, 2 to 20, 2 to 15, 2 to 10, or 2 to 5 single crystal particles. Here, the "single-crystal particle" refers to the smallest unit of a particle that can be recognized when observing the positive electrode active material through a scanning electron microscope.

[0034] In this specification, the average particle size (D 50 The average particle size (D) refers to the particle size at 50% of the volume cumulative particle size distribution of the positive electrode active material precursor, the positive electrode active material, or the lithium transition metal oxide powder. 50 ) can be measured using the laser diffraction method. For example, the positive electrode active material powder is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac MT 3000), and ultrasonic waves of about 28 kHz are irradiated at an output of 60 W. Then, a volume cumulative particle size distribution graph is obtained, and the particle diameter corresponding to 50% of the volume cumulative amount is obtained.

[0035] In this specification, the average grain size of the single crystal grains (D EBSD ) refers to the particle size at 50% of the volume cumulative particle size distribution of single crystal particles obtained by EBSD analysis using SEM. The EBSD analysis can be performed by acquiring images using SEM-EBSD equipment (e.g., FEI's Quanta200-EDAX's Velocity super OIM 8), and analyzing the images using image analysis software (EDAX OIM Analysis).

[0036] The present invention will be described in detail below.

[0037] positive electrode active material The present invention relates to a positive electrode active material in the form of a single particle, and to a positive electrode including a positive electrode active material layer containing the positive electrode active material in an amount of 80% by weight or more based on the total weight of the positive electrode active material layer, the positive electrode active material layer being rolled so that the density of the positive electrode active material layer after rolling is 2.7 g / cm 3 When the positive electrode active material layer is analyzed by XRD after being rolled to the above value, the ratio of the (003) peak area to the areas of all peaks observed in the 2θ 10° to 90° range is 30% or more.

[0038] In the present invention, the rolling is performed so that the electrode density of the positive electrode active material layer after rolling is 2.7 g / cm 3 Specifically, 2.7 g / cm 3 ~3.0g / cm 3 Specifically, the rolling may be performed by a roll pressing method so that the electrode density of the positive electrode active material layer after rolling is 2.7 g / cm. 3 The method may be roll pressing to obtain a molded product.

[0039] The positive electrode active material according to the present invention is a positive electrode including a positive electrode active material layer containing a positive electrode active material in an amount of 80% by weight or more based on the total weight of the positive electrode active material layer, the positive electrode active material layer being rolled so that the density of the positive electrode active material layer after rolling is 2.7 g / cm 3 or more, and then analyzing the positive electrode active material layer by XRD, the ratio of the area of ​​the (003) peak to the area of ​​all peaks observed in the 2θ range of 10° to 90° can satisfy 30% or more, specifically, 50%, 60% or more, 85%, or 95% or less.

[0040] The (003) plane is the direction in which lithium moves, and the normal direction of the (003) plane is the c-axis direction (hereinafter, c-axis direction) of the crystal structure, which is the contraction / expansion direction of the positive electrode active material crystal. Therefore, when the above conditions are met, when the positive electrode active material according to the present invention is applied to a positive electrode, the c-axis direction of the positive electrode active material crystal contained in the positive electrode active material layer is aligned in a direction perpendicular to the upper surface (or electrode surface) of the current collector. As a result, when a positive electrode including the positive electrode active material according to the present invention is applied to a battery, the expansion of the positive electrode active material crystal in the c-axis direction is suppressed by an external case, etc., and the life performance of the battery is improved. Meanwhile, during XRD measurement, the sample is positioned so that X-rays are incident in the direction of the positive electrode active material layer, not in the direction of the current collector.

[0041] According to the present invention, the cathode active material according to the present invention may satisfy a ratio difference of the (003) peak area to the area of ​​all peaks observed in the 2θ 10° to 90° range when the cathode active material layer before and after rolling the cathode including the cathode active material layer containing 80 wt% or more of the cathode active material based on the total weight of the cathode active material layer is analyzed by XRD, which is 10%, 20%, 30% or more, and 75% or less. That is, the difference between the ratio of the (003) peak area to the area of ​​all peaks observed in the 2θ 10° to 90° range when the cathode active material layer of the cathode before rolling is analyzed by XRD and the ratio of the (003) peak area to the area of ​​all peaks observed in the 2θ 10° to 90° range when the cathode active material layer of the cathode after rolling is analyzed by XRD may be 10%, 20%, 30% or more, and 75% or less. In this case, the c-axis direction, which is the contraction / expansion direction of the positive electrode active material crystals, is aligned in a direction perpendicular to the upper surface (or electrode surface) of the current collector, which has the effect of improving the life performance of the battery.

[0042] When the positive electrode active material layer before rolling the positive electrode is analyzed by XRD, the ratio of the area of ​​a (003) peak to the area of ​​all peaks observed in the 2θ range of 10° to 90° may be 10%, 20% or more, 40%, or 49% or less.

[0043] The positive electrode active material in the form of a single particle has an average particle size (D 50Specifically, the average particle diameter (D 50 ) may be 0.1 μm, 1.0 μm, 2.0 μm or more and 5.0 μm, 6.0 μm, 7.0 μm, 8.0 μm, 9.0 μm, 10.0 μm or less. In this case, the rolling ratio of the battery including the positive electrode active material in the form of single particles can be increased, and the battery performance can be further improved.

[0044] According to the present invention, the single-particle positive electrode active material may be composed of 1 to 50 single crystal particles for aligning the c-axis direction, which is the contraction / expansion direction of the positive electrode active material crystal, with the lithium transport path. Specifically, the single-particle positive electrode active material may be composed of 1 to 5, 10, 20, 30, 40, or 50 single crystal particles.

[0045] According to the present invention, the single crystal particles have an average particle size (D EBSD ) may be 0.1 μm to 10 μm, specifically, 0.1 μm, 0.2 μm or more, 5 μm, 8 μm, or 10 μm or less. In this case, it is possible to prevent the slurry (composition for forming a positive electrode active material layer) from coagulating or gelling during the manufacture of the electrode, and it is possible to reduce the occurrence of cracks in the particles during the process of repeating charge and discharge.

[0046] According to the present invention, the positive electrode active material in the form of a single particle may be a lithium composite transition metal oxide including nickel (Ni), cobalt (Co) and manganese (Mn), wherein the lithium composite transition metal oxide may include 60 mol % to 65 mol % or more of nickel (Ni) among all metals other than lithium.

[0047] According to the present invention, the lithium composite transition metal oxide may have a composition represented by the following Chemical Formula 1.

[0048] [Chemical formula 1] Li a Ni b Co c Mn dM 1 e O2

[0049] In the above Chemical Formula 1, M 1 is one or more selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S; 0.90≦a≦1.1, 0.60≦b<1.0, 0 <c<0.40、0<d<0.40、0≦e≦0.10、b+c+d+e=1である。

[0050] The b means the atomic fraction of nickel among metal elements other than lithium in the lithium composite transition metal oxide, and may be 0.60, 0.65, 0.8, or 0.85 or more and 0.95 or 0.98 or less.

[0051] The c means the atomic fraction of cobalt among metal elements other than lithium in the lithium composite transition metal oxide, and may be 0.01 or more and 0.10, 0.20, 0.30, or 0.40 or less.

[0052] The d indicates the atomic fraction of manganese among metal elements other than lithium in the lithium composite transition metal oxide, and may be 0.01 or more and 0.10, 0.20, 0.30, or 0.40 or less.

[0053] The e is M among the metal elements other than lithium in the lithium composite transition metal oxide. 1 It means the element fraction of an element, and can be 0 or more and 0.02, 0.05, 0.10 or less.

[0054] Here, the positive electrode active material may be contained in a content of 80% by weight to 99% by weight, more specifically, 85% by weight to 98% by weight, based on the total weight of the positive electrode active material layer. When contained in the above content range, excellent capacity characteristics can be exhibited.

[0055] positive electrode The present invention provides a positive electrode including a current collector and a positive electrode active material layer located on the current collector, the positive electrode active material layer including the positive electrode active material according to the present invention. That is, the present invention provides a positive electrode including a current collector and a positive electrode active material layer located on the current collector, the positive electrode active material layer including 80 wt% or more of a single particle positive electrode active material based on the total weight of the positive electrode active material layer, and when the positive electrode is rolled and the positive electrode active material layer is analyzed by XRD, the ratio of the area of ​​a (003) peak to the area of ​​all peaks observed in the 2θ 10° to 90° range is 30% or more.

[0056] In the present invention, the rolling is performed so that the electrode density of the positive electrode active material layer after rolling is 2.7 g / cm 3 Specifically, 2.7 g / cm 3 ~3.0g / cm 3 Specifically, the rolling may be performed by a roll pressing method so that the electrode density of the positive electrode active material layer after rolling is 2.7 g / cm. 3 The method may be roll pressing to obtain a molded product.

[0057] Specifically, the positive electrode includes a positive electrode current collector and a positive electrode active material layer located on at least one surface of the positive electrode current collector and including a positive electrode active material in the form of a single particle. In addition, when the positive electrode is rolled and the positive electrode active material layer is analyzed by XRD, the ratio of the area of ​​a (003) peak to the area of ​​all peaks observed in the 2θ 10° to 90° range is 30% or more. Specifically, when the positive electrode is rolled and the positive electrode active material layer is analyzed by XRD, the ratio of the area of ​​a (003) peak to the area of ​​all peaks observed in the 2θ 10° to 90° range may be 50%, 60% or more, 85%, or 95% or less.

[0058] The (003) plane is the direction in which lithium moves, and the normal direction of the (003) plane is the c-axis direction (hereinafter, c-axis direction) of the crystal structure, which is the contraction / expansion direction of the positive electrode active material crystal. Therefore, when the above conditions are met, the c-axis direction of the positive electrode active material crystal contained in the positive electrode active material layer is aligned in a direction perpendicular to the upper surface (or electrode surface) of the current collector, and as a result, when the positive electrode according to the present invention is applied to a battery, the expansion of the positive electrode active material crystal in the c-axis direction is suppressed by the external case, etc., and the life performance of the battery is improved. Meanwhile, during XRD measurement, the sample is positioned so that X-rays are incident in the direction of the positive electrode active material layer, not in the direction of the current collector.

[0059] According to the present invention, when the positive electrode active material layer before and after rolling of the positive electrode is analyzed by XRD, the difference in the ratio of the (003) peak area to the area of ​​all peaks observed in the 2θ 10° to 90° range may be 10%, 20%, 30% or more, and 75% or less. That is, the difference between the ratio of the (003) peak area to the area of ​​all peaks observed in the 2θ 10° to 90° range when the positive electrode active material layer of the positive electrode before rolling is analyzed by XRD and the ratio of the (003) peak area to the area of ​​all peaks observed in the 2θ 10° to 90° range when the positive electrode active material layer of the positive electrode after rolling is analyzed by XRD may be 10%, 20%, 30% or more, and 75% or less. In this case, the c-axis direction, which is the contraction / expansion direction of the positive electrode active material crystals, is aligned in a direction perpendicular to the upper surface (or electrode surface) of the current collector, which has the effect of improving the life performance of the battery.

[0060] When the positive electrode active material layer before rolling the positive electrode is analyzed by XRD, the ratio of the area of ​​a (003) peak to the area of ​​all peaks observed in the 2θ range of 10° to 90° may be 10%, 20% or more, 40%, or 49% or less.

[0061] In addition, in the positive electrode, when the angle between the lithium migration path of the positive electrode active material in the form of a single particle and an axis parallel to the upper surface of the current collector is θ, (cosθ) 2 The value of (cosθ) is 0.6 or more. 2The value can be 0.6 or more and 0.7, 0.8, 0.9, or 1 or less. In this case, the life performance of the battery can be further improved.

[0062] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it can be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0063] The positive electrode active material layer may include a positive electrode active material in the form of single particles, a conductive material, and a binder.

[0064] According to the present invention, the single particle type positive electrode active material may have a c-axis direction of the crystal aligned perpendicular to the top surface of the current collector. In this case, the c-axis direction, which is the contraction / expansion direction of the positive electrode active material crystal, is aligned perpendicular to the top surface (or electrode surface) of the current collector, and when the positive electrode is applied to a battery, the expansion of the positive electrode active material crystal in the c-axis direction is suppressed by an external case, etc., and thus the life performance can be further improved.

[0065] According to the present invention, the single particle positive electrode active material may have a ratio of the length in the a-axis direction to the length in the c-axis direction of the crystals so that the c-axis direction, which is the contraction / expansion direction of the positive electrode active material crystals, is aligned in a direction perpendicular to the upper surface (or electrode surface) of the current collector, and may have a size greater than 1. That is, the single particle positive electrode active material may have a shape in which the particle length is short in one direction, specifically, in the c-axis direction.

[0066] According to the present invention, the single-particle positive electrode active material may be composed of 1 to 50 single crystal particles for alignment of the c-axis direction, which is the contraction / expansion direction of the positive electrode active material crystal, with the lithium migration path. Specifically, the single-particle positive electrode active material may be composed of 1 or more, 5, 10, 20, 30, 40, or 50 or less single crystal particles.

[0067] According to the present invention, the single crystal particles have an average particle size (D EBSD ) can be 0.1 μm to 10 μm, specifically 0.1 μm, 0.2 μm or more, 5 μm, 8 μm, or 10 μm or less. In this case, it is possible to prevent the slurry (composition for forming a positive electrode active material layer) from coagulating or gelling during the production of the electrode, and it is possible to reduce the occurrence of cracks in the particles during the process of repeated charging and discharging.

[0068] According to the present invention, the positive electrode active material in the form of a single particle may be a lithium composite transition metal oxide containing nickel (Ni), cobalt (Co) and manganese (Mn), wherein the lithium composite transition metal oxide may contain 60 mol % to 65 mol % or more of nickel (Ni) among all metals other than lithium.

[0069] According to the present invention, the lithium composite transition metal oxide may have a composition represented by the following Chemical Formula 1.

[0070] [Chemical formula 1] Li a Ni b Co c Mn d M 1 e O2

[0071] In the above Chemical Formula 1, M 1 is one or more selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S; 0.90≦a≦1.1, 0.60≦b<1.0, 0 <c<0.40、0<d<0.40、0≦e≦0.10、b+c+d+e=1である。

[0072] The b means the atomic fraction of nickel among metal elements other than lithium in the lithium composite transition metal oxide, and may be 0.60, 0.65, 0.8, or 0.85 or more and 0.95 or 0.98 or less.

[0073] The c means the atomic fraction of cobalt among metal elements other than lithium in the lithium composite transition metal oxide, and may be 0.01 or more and 0.10, 0.20, 0.30, or 0.40 or less.

[0074] The d indicates the atomic fraction of manganese among metal elements other than lithium in the lithium composite transition metal oxide, and may be 0.01 or more and 0.10, 0.20, 0.30, or 0.40 or less.

[0075] The e is M among the metal elements other than lithium in the lithium composite transition metal oxide. 1 It means the element fraction of an element, and can be 0 or more and 0.02, 0.05, 0.10 or less.

[0076] Here, the positive electrode active material may be contained in a content of 80% by weight to 99% by weight, more specifically, 85% by weight to 98% by weight, based on the total weight of the positive electrode active material layer. When contained in the above content range, excellent capacity characteristics can be exhibited.

[0077] The conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and one or more of these can be used alone or in combination. The conductive material can be contained in an amount of 1% by weight to 30% by weight based on the total weight of the positive electrode active material layer.

[0078] Here, the conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it does not cause a chemical change in the battery that is constructed and has electronic conductivity. Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fibers; metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive polymers such as polyphenylene derivatives, and among these, one type alone or a mixture of two or more types can be used. The conductive material can be contained in an amount of 1% by weight to 30% by weight based on the total weight of the positive electrode active material layer.

[0079] The positive electrode can be manufactured by a normal method for manufacturing a positive electrode, except for using the positive electrode active material described above. Specifically, the positive electrode can be manufactured by applying a composition (slurry) for forming a positive electrode active material layer, which is manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent, onto a positive electrode current collector, followed by drying and rolling. Here, the types and contents of the positive electrode active material, binder, and conductive material are as described above. In addition, as another method, the positive electrode can also be manufactured by casting the composition for forming a positive electrode active material layer onto another support, peeling it off from the support, and laminating the film obtained on the positive electrode current collector.

[0080] The solvent may be a solvent commonly used in the art, and may include dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity during subsequent coating for the production of a positive electrode, taking into consideration the coating thickness of the slurry and the manufacturing yield.

[0081] Lithium secondary battery In addition, the present invention can provide an electrochemical device including the positive electrode. The electrochemical device can be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0082] Specifically, the lithium secondary battery includes a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Since the positive electrode is as described above, a detailed description thereof will be omitted, and only the remaining components will be described in detail below.

[0083] Also, the lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0084] In the lithium secondary battery, the negative electrode includes a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0085] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon, copper or stainless steel surface treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may have a thickness of usually 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0086] The negative electrode active material layer includes a negative electrode active material, and optionally a binder and a conductive material.

[0087] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a thin film of metallic lithium may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0088] The negative electrode active material may be included in an amount of 80% by weight to 99% by weight based on the total weight of the negative electrode active material layer.

[0089] The binder is a component that facilitates bonding between the conductive material, the active material, and the current collector, and can usually be added in an amount of 0.1% by weight to 10% by weight based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0090] The conductive material is a component for further improving the conductivity of the negative electrode active material, and may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of such conductive materials include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0091] The negative electrode active material layer can be produced by applying a composition for forming a negative electrode active material layer, which is prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent, onto a negative electrode current collector and drying the composition. Alternatively, the negative electrode active material layer can be produced by casting the composition for forming a negative electrode active material layer onto a separate support, peeling it off from the support, and laminating the resulting film onto the negative electrode current collector.

[0092] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode and provides a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery can be used without any particular limitation. In particular, a separator that has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability is preferable. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof can be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. can be used. In addition, a coated separator containing a ceramic component or a polymeric material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single layer or multilayer structure.

[0093] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0094] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0095] The organic solvent can be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent can be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone; an ether solvent such as dibutyl ether or tetrahydrofuran; a ketone solvent such as cyclohexanone; an aromatic hydrocarbon solvent such as benzene or fluorobenzene; dimethylcarbonate (DMC), diethylcarbonate (DEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Carbonate-based solvents such as ethylene carbonate (PC); alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; or sulfolanes may be used. Among them, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the cyclic carbonate and the linear carbonate are mixed in a volume ratio of about 1:1 to about 1:9, so that the electrolyte can exhibit excellent performance.

[0096] The lithium salt can be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt can be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt is preferably used within a concentration range of 0.1M to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, and therefore can exhibit excellent electrolyte performance, and lithium ions can move effectively.

[0097] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, in order to improve the life characteristics of the battery, suppress the decrease in the capacity of the battery, and improve the discharge capacity of the battery. In this case, the additives may be contained in an amount of 0.1% by weight to 5% by weight based on the total weight of the electrolyte.

[0098] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in portable devices such as mobile phones, notebook computers and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0099] Therefore, according to another embodiment of the present invention, there is provided a battery module including the lithium secondary battery as a unit cell, and a battery pack including the same.

[0100] The battery module or battery pack may be used as a power source for one or more medium- to large-sized devices, such as a power tool; an electric vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV); or a power storage system.

[0101] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.

[0102] The lithium secondary battery according to the present invention can be used not only as a battery cell used as a power source for a small device, but also as a unit battery for a medium- to large-sized battery module including a large number of battery cells.

[0103] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will now be described in detail with reference to exemplary embodiments thereof, so that those skilled in the art can easily practice the present invention. However, the present invention may be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.

[0104] Examples and Comparative Examples Example 1 Ni 0.95 Co 0.03 Mn 0.02 It has a composition represented by (OH)2 and an average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and the mixture was subjected to primary firing at a temperature of 870° C. for 9 hours in an oxygen atmosphere to produce a pre-fired product. The pre-fired product was crushed and then subjected to secondary firing at a temperature of 750° C. for 9 hours in an oxygen atmosphere to produce LiNi 0.95 Co 0.03 Mn0.02 A lithium transition metal composite oxide in the form of a single particle and having a composition represented by O2 was produced.

[0105] The prepared lithium transition metal composite oxide in the form of single particles was mixed with powdered Co(OH)2 (manufactured by HUAYOU COBALT) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700°C for 5 hours in an oxygen atmosphere to prepare a positive electrode active material in the form of single particles.

[0106] Example 2 Ni 0.88 Co 0.03 Mn 0.09 It has a composition represented by (OH)2 and an average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and the mixture was subjected to primary firing at a temperature of 900° C. for 9 hours in an oxygen atmosphere to produce a pre-fired product. The pre-fired product was crushed and then subjected to secondary firing at a temperature of 780° C. for 9 hours in an oxygen atmosphere to produce LiNi 0.88 Co 0.03 Mn 0.09 A lithium transition metal composite oxide in the form of a single particle and having a composition represented by O2 was produced.

[0107] The prepared lithium transition metal composite oxide in the form of single particles was mixed with powdered Co(OH)2 (manufactured by HUAYOU COBALT) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at a temperature of 700°C for 5 hours in an oxygen atmosphere to prepare a positive electrode active material in the form of single particles.

[0108] Comparative Example 1 Ni 0.95 Co 0.03 Mn 0.02 It has a composition represented by (OH)2 and an average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and the mixture was subjected to primary firing at a temperature of 800° C. for 9 hours in an oxygen atmosphere to produce a pre-fired product. The pre-fired product was crushed and then subjected to secondary firing at a temperature of 750° C. for 9 hours in an oxygen atmosphere to produce LiNi 0.95 Co 0.03 Mn 0.02A lithium transition metal composite oxide having a composition represented by O2 and an intermediate form between the single particle form and the secondary particle form was produced.

[0109] The prepared single particle lithium composite transition metal oxide was mixed with powdered Co(OH)2 (manufactured by HUAYOU COBALT) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at 700°C for 5 hours in an oxygen atmosphere to prepare a positive electrode active material that is an intermediate form between the single particle form and the secondary particle form.

[0110] Comparative Example 2 Ni 0.88 Co 0.03 Mn 0.09 It has a composition represented by (OH)2 and an average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and the mixture was subjected to primary firing at a temperature of 820° C. for 9 hours in an oxygen atmosphere to produce a pre-fired product. The pre-fired product was crushed and then subjected to secondary firing at a temperature of 780° C. for 9 hours in an oxygen atmosphere to produce LiNi 0.88 Co 0.03 Mn 0.09 A lithium transition metal composite oxide having a composition represented by O2 and an intermediate form between the single particle form and the secondary particle form was produced.

[0111] The prepared single particle lithium composite transition metal oxide was mixed with powdered Co(OH)2 (manufactured by HUAYOU COBALT) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at 700°C for 5 hours in an oxygen atmosphere to prepare a positive electrode active material that is an intermediate form between the single particle form and the secondary particle form.

[0112] Comparative Example 3 Ni 0.95 Co 0.03 Mn 0.02 It has a composition represented by (OH)2 and an average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and calcined at 750° C. for 9 hours in an oxygen atmosphere to obtain LiNi 0.95 Co 0.03 Mn 0.02A lithium composite transition metal oxide having a composition represented by O2 was produced.

[0113] The lithium transition metal composite oxide in the form of single particles was mixed with powdered Co(OH)2 (manufactured by HUAYOU COBALT) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at 700°C for 5 hours in an oxygen atmosphere to prepare a positive electrode active material in the form of secondary particles.

[0114] Comparative Example 4 Ni 0.88 Co 0.03 Mn 0.09 It has a composition represented by (OH)2 and an average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05 and calcined at 800° C. for 9 hours in an oxygen atmosphere to obtain LiNi 0.88 Co 0.03 Mn 0.09 A lithium composite transition metal oxide having a composition represented by O2 was produced.

[0115] The lithium transition metal composite oxide in the form of single particles was mixed with powdered Co(OH)2 (manufactured by HUAYOU COBALT) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at 700°C for 5 hours in an oxygen atmosphere to prepare a positive electrode active material in the form of secondary particles.

[0116] Comparative Example 5 Ni 0.88 Co 0.03 Mn 0.09 It has a composition represented by (OH)2 and an average particle size (D 50 The positive electrode active material precursor having a particle size of 3.5 μm was mixed with LiOH in a molar ratio of 1:1.05, and calcined at 840° C. for 9 hours in an oxygen atmosphere to obtain LiNi 0.88 Co 0.03 Mn 0.09 A lithium composite transition metal oxide having a composition represented by O2 was produced.

[0117] The lithium composite transition metal oxide thus prepared was mixed with powdered Co(OH)2 (manufactured by HUAYOU COBALT) in a molar ratio of 1:0.02 to prepare a mixture. The mixture was heat-treated at 700°C for 5 hours in an oxygen atmosphere to prepare a positive electrode active material in the form of secondary particles.

[0118] Experimental Example Experimental example 1: SEM image analysis The positive electrode active materials of Example 1, Comparative Example 1, and Comparative Example 3 were measured using a scanning electron microscope (SEM) (JEOL, JSM-7900F; accelerating voltage 20 kV), and SEM images of each were obtained and shown in Figures 1, 2, and 3, respectively.

[0119] FIG. 1 is an SEM image of the positive electrode active material of Example 1, FIG. 2 is an SEM image of the positive electrode active material of Comparative Example 1, and FIG.

[0120] 1 to 3, the positive electrode active material of Example 1 has a single particle form with one to a few particles (average particle size (D EBSD ) is 1.5 μm), whereas the positive electrode active material of Comparative Example 3 is in the form of secondary particles, and the positive electrode active material of Comparative Example 1 is in the form intermediate between the single particle form and the secondary particle form defined in the present invention.

[0121] Experimental example 2: XRD data analysis (Preparation of electrode samples for analysis) The positive electrode active materials produced in Examples 1 and 2 and Comparative Examples 1 to 4, a conductive carbon black (DenkaBlack, manufactured by Denka Corporation) and a binder PVdF (KF1300, manufactured by Kureha Corporation) were added in a weight ratio of 95:3:2 to an N-methylpyrrolidone (NMP) (manufactured by Oi Chemical Industries, Ltd.) solvent to produce compositions for forming a positive electrode active material layer.

[0122] The positive electrode active material layer-forming composition was applied to one surface of an aluminum foil current collector having a thickness of 20 μm, and dried at a temperature of 135° C. for 3 hours to form a positive electrode active material layer. Then, the electrode density of the positive electrode active material layer after rolling was 2.7 g / cm3 The mixture was rolled by a roll press method to prepare a positive electrode.

[0123] For reference, electrode density is the mass of the positive electrode active material per unit area of ​​the electrode (excluding the weight of the conductive material, binder, and current collector) divided by the unit volume of the electrode (thickness excluding the current collector x unit area).

[0124] (XRD Measurement and Analysis) Using an Empyrean XRD device manufactured by Panalytical (Cu-target, voltage: 45 kV, current: 40 mA, 2θ: 10° to 90°), XRD data of the positive electrode active material layers before and after rolling of the positive electrodes including the positive electrode active materials of Examples 1 and 2 and Comparative Examples 1 to 4 were obtained and shown in Figure 4. The ratios of the area of ​​the (003) peak to the areas of all peaks observed in the 2θ 10 to 90° range are shown in Table 1 below.

[0125] [Table 1]

[0126] 4, it can be seen that in Examples 1 and 2, the area ratio of the (003) peak is higher both before and after rolling compared to Comparative Examples 3 and 4. In particular, it can be seen that the difference between before and after rolling is very large due to the rearrangement of particles during the rolling process, and the value after rolling is also significantly different from Comparative Examples 3 and 4.

[0127] Example 3: EBSD data analysis An electrode sample for analysis was prepared in the same manner as in Experimental Example 2, and the positive electrode was irradiated with an argon (Ar) ion beam using HITACHI's IM5000 (accelerating voltage: 6 kV), cut by ion milling to obtain a cross section of the positive electrode, and the cross section of the positive electrode was measured and analyzed using JEOL's JSM-7900F (accelerating voltage: 20 kV). AztecCrystal manufactured by OXFORD Instruments was used as the image processing-EBSD quantification analysis software.

[0128] Figure 5 is an EBSD Band Contrast (BC) image of a cross section of a positive electrode containing the positive electrode active material of Example 1. In (A) of Figure 5, the long axis of the particle is indicated by a red arrow, and in (B) of Figure 5, a crystal grain model based on the crystal orientation is shown in the shape of a hexagonal column (the long direction of the crystal structure model represents the c-axis). In the EBSD BC image, the vertical direction (Y1) is the direction perpendicular to the electrode, and the horizontal direction (X1) is the direction parallel to the electrode.

[0129] For reference, the image in Figure 5 is a cross section, and in fact, in a three-dimensional particle, the length of the particle in any one axial direction is longer than the other two axes.

[0130] The angle between the c-axis vector (Euler angle) of all crystal grains (approximately 50 to 100 grains) in the image obtained by EBSD analysis and the directional vector perpendicular to the electrode (= the angle between the lithium migration path (Li path) and the directional vector parallel to the electrode) is defined as θ, and the (cosθ) of each crystal grain is 2 Calculate the value of (cosθ) for all grains. 2 The average values ​​of are shown in Table 2 below, and the lithium transport path of the positive electrode active material and the degree of electrode alignment were confirmed.

[0131] Figure 6 shows the angle between the c-axis vector (Euler angle) of the crystal grain and the vector perpendicular to the electrode (= the angle between the lithium migration path (Li path) and the vector parallel to the electrode), and (cosθ) 2It is considered that the closer the value of is to 1, the more parallel the lithium migration path is to the electrode surface direction.

[0132] [Table 2]

[0133] Experimental Example 4: Evaluation of battery characteristics (Half-cell manufacturing) The positive electrode active materials produced in Examples 1 and 2 and Comparative Examples 1 to 4, a conductive carbon black (DenkaBlack, manufactured by Denka Corporation) and a binder PVdF (KF1300, manufactured by Kureha Corporation) were added in a weight ratio of 95:3:2 to an N-methylpyrrolidone (NMP) (manufactured by Oi Chemical Industries, Ltd.) solvent to produce compositions for forming a positive electrode active material layer.

[0134] The positive electrode active material layer-forming composition was applied to one side of an aluminum foil current collector having a thickness of 20 μm, and dried at a temperature of 135° C. for 3 hours to form a positive electrode active material layer. Then, the positive electrode active material layer was rolled by a roll press method so that the porosity of the positive electrode active material layer after rolling was 20% by volume, thereby manufacturing a positive electrode.

[0135] Along with the positive electrode, a half-cell was fabricated using lithium metal as the negative electrode.

[0136] (1) Initial resistance (DCIR) evaluation The half cells prepared above were charged at 25° C. at a constant current (CC) of 0.2 C up to 4.25 V, then charged at a constant voltage (CV) of 4.25 V until the charging current reached 0.05 mAh (cut-off current), and then discharged at a constant current of 0.2 C for 10 seconds. The initial resistance was calculated by dividing the voltage difference between the fully charged state and 10 seconds after the start of discharge by the current, and the results are shown in Table 3 below.

[0137] (2) Evaluation of capacity retention rate and resistance increase rate The half cells prepared above were charged at 25° C. at a constant current (CC) of 0.2 C up to 4.25 V, then charged at a constant voltage (CV) of 4.25 V until the charging current reached 0.05 mAh (cut-off current), and then left for 20 minutes, after which they were discharged at a constant current of 0.2 C down to 2.5 V.

[0138] The cell was then transferred to a chamber at 45°C, charged to 4.25V at a constant current of 0.33C, then charged at a constant voltage (CV) of 4.25V, charged until the charge current reached 0.05mAh (cut-off current), and then discharged to 2.5V at a constant current of 0.33C, with 30 cycles of charge and discharge being performed. Here, the percentage of the discharge capacity at the 30th cycle relative to the discharge capacity at the first cycle was taken as the capacity retention rate, and is shown in Table 3 below. In addition, the percentage of the DCIR value at the 30th cycle relative to the DCIR value at the first cycle was taken as the resistance increase rate, and is shown in Table 3 below. For reference, the DCIR value at the nth cycle was calculated by dividing the voltage difference between the fully charged state and 10 seconds after the start of discharge, which was obtained while discharging to 2.5V at a constant current of 0.33C in the nth cycle, by the current.

[0139] [Table 3]

[0140] Referring to Tables 1 to 3, it can be seen that the positive electrodes including the positive electrode active materials in the form of single particles of Examples 1 and 2, in which the ratio of the area of ​​the (003) peak to the area of ​​all peaks observed in the 2θ 10 to 90° range is 30% or more when the positive electrode is rolled and the positive electrode active material layer is analyzed by XRD, have excellent initial resistance characteristics and life characteristics compared to the positive electrodes including the positive electrode active materials in the form of secondary particles of Comparative Examples 3 and 4 and the positive electrodes including the positive electrode active materials in the form of intermediate between the single particle form and the secondary particle form of Comparative Examples 1 and 2. It can also be seen that the positive electrodes including the positive electrode active materials in the form of single particles of Examples 1 and 2 have significantly better life characteristics compared to the positive electrode active material of Comparative Example 5, in which several hundred primary particles are aggregated and the single particle form are mixed.

Claims

1. A positive electrode active material in a single particle form, A positive electrode including a positive electrode active material layer containing the positive electrode active material in an amount of 80% by weight or more based on the total weight of the positive electrode active material layer is rolled to have a density of the positive electrode active material layer of 2.7 g / cm 3 or more, and then analyzing the positive electrode active material layer by XRD, the ratio of the area of ​​the (003) peak to the area of ​​all peaks observed in the 2θ range of 10° to 90° is 30% or more.

2. 2. The cathode active material according to claim 1, wherein, when the cathode active material layer before and after rolling is analyzed by XRD, a ratio difference of an area of ​​a (003) peak to an area of ​​all peaks observed in a 2θ range of 10° to 90° is 10% or more.

3. The positive electrode active material according to claim 1, wherein the single-particle positive electrode active material has a ratio of the length in the a-axis direction of the crystal to the length in the c-axis direction of the crystal greater than 1.

4. The positive electrode active material according to claim 1, wherein the positive electrode active material in single particle form is composed of 1 to 50 single crystal particles.

5. The single crystal particles have an average particle size (D EBSD 5. The positive electrode active material according to claim 4, wherein the average particle diameter is 0.1 μm to 10 μm.

6. The positive electrode active material according to claim 1 , wherein the positive electrode active material in the form of single particles is a lithium transition metal composite oxide containing nickel (Ni), cobalt (Co), and manganese (Mn).

7. The positive electrode active material according to claim 6 , wherein the lithium composite transition metal oxide contains nickel (Ni) in an amount of 60 mol % or more of all metals other than lithium.

8. The positive electrode active material according to claim 6 , wherein the lithium composite transition metal oxide has a composition represented by the following Chemical Formula 1: [Chemical formula 1] Li a Ni b Co c Mn d M 1 e O 2 In the above Chemical Formula 1, M 1 is one or more selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S; 0.90≦a≦1.1, 0.60≦b<1.0, 0<c<0.40, 0<d<0.40, 0≦e≦0.10, and b+c+d+e=1.

9. A current collector; a positive electrode active material layer located on the current collector, The positive electrode, wherein the positive electrode active material layer comprises the positive electrode active material according to claim 1 .

10. 10. The positive electrode according to claim 9, wherein, when the positive electrode active material layer before and after rolling is analyzed by XRD, a ratio difference of an area of ​​a (003) peak to an area of ​​all peaks observed in a 2θ range of 10° to 90° is 10% or more.

11. When the angle between the lithium migration path of the single particle positive electrode active material and the axis parallel to the upper surface of the current collector is θ, (cosθ) 2 10. The positive electrode of claim 9, wherein the value is 0.6 or greater.

12. The positive electrode according to claim 9 , wherein the positive electrode active material in single particle form has a crystal c-axis direction aligned in a direction perpendicular to an upper surface of a current collector.

13. The positive electrode according to claim 9, wherein the positive electrode active material in single particle form has a ratio of the length in the a-axis direction of the crystal to the length in the c-axis direction of the crystal greater than 1.

14. The positive electrode according to claim 9, wherein the positive electrode active material in single particle form is composed of 1 to 50 single crystal particles.

15. The single crystal particles have an average particle size (D EBSD 15. The positive electrode of claim 14, wherein the thickness of the first electrode is 0.1 μm to 10 μm.

16. The positive electrode according to claim 9 , wherein the positive electrode active material in the form of single particles is a lithium composite transition metal oxide containing nickel (Ni), cobalt (Co) and manganese (Mn).

17. The positive electrode according to claim 16, wherein the lithium composite transition metal oxide contains nickel (Ni) in an amount of 60 mol % or more of all metals other than lithium.

18. The positive electrode according to claim 16 , wherein the lithium composite transition metal oxide has a composition represented by the following Chemical Formula 1: [Chemical formula 1] Li a Ni b Co c Mn d M 1 e O 2 In the above Chemical Formula 1, M 1 is one or more selected from Al, Zr, B, W, Mo, Cr, Nb, Mg, Hf, Ta, La, Ti, Sr, Ba, Ce, Sn, Y, Zn, F, P, and S; 0.90≦a≦1.1, 0.60≦b<1.0, 0<c<0.40, 0<d<0.40, 0≦e≦0.10, and b+c+d+e=1.

Citation Information

Patent Citations

  • Nonaqueous electrolyte battery, positive active material thereof, and manufacture of positive plate

    JP1997022693A

  • All-solid lithium battery and method of manufacturing the same

    JP2019192609A

  • Lithium-ion secondary cell and method for manufacturing same

    WO2016152876A1